Aprimoramento de rotas e produção de dosímetros à base de CaSO4 com dopagens não usuais - Junot, Danilo Oliveira (2017)
The widespread use of ionizing radiation in medicine and industry, associated with the known risks that this type of radiation can cause, has motivated the search for new radiation detectors, seeking improvements in the dosimetric characteristics and in the cost of production in comparison with commercial dosimeters disseminated. The motivation of this work is, therefore, to produce new thermoluminescent detectors through improved routes. Unusual elements in CaSO 4 matrix doping, such as terbium (Tb) and ytterbium (Yb), were used as dopants in this matrix, as well as the europium (Eu), the thulium (Tm) and the silver (Ag), resulting in samples of CaSO 4 :Eu,Tb, CaSO 4 :Tb,Yb, CaSO 4 :Tm,Ag and CaSO 4 :Eu,Ag that were prepared by means of an adaptation of the method developed by Yamashita (1971). The route of synthesis is based on the mixture of calcium carbonate (CaCO 3 ) and dopant oxide (except for silver, incorporated in the form of metalic nanoparticles) in a solution of sulfuric acid. The mixture is heated until all the acid evaporates and only the powder of the material remains. In this route, the sulfuric acid is collected and can be reused. The phosphors produced were characterized by X-ray diffraction and radioluminescence techniques. The silver particles, produced by the polyol method, were characterized by scanning electron microscopy. Composites were obtained from the addition of Teflon to the phosphors. The thermoluminescence (TL) and the optically stimulated luminescence (OSL) of the new materials produced were investigated. Thermoluminescent characteristics such as sensitivity, linearity, reproducibility, minimum detectable dose, kinetic order and fading were evaluated and discussed. The CaSO 4 :Tb,Eu composites showed TL glow curves with peaks at temperatures of 170 °C, 270 °C and 340 °C. The CaSO 4 :Tb,Yb composites presented TL glow curves with peaks at temperatures of 90 °C, 160 °C, 240 °C and 340 °C. CaSO 4 :Tm showed peaks at temperatures of 140 °C and 225 °C and the CaSO 4 :Tm,Ag presented peaks at temperatures of 140 °C, 280 °C and 380 °C. All composites showed a linear and reproducible dose response. The TL emission spectrum of the composites was also evaluated. The samples of calcium sulfate doped with europium and silver particles (CaSO 4 :Eu,Ag) showed great potential for applicability in the OSL dosimetry.